Low Intakes of Iodine and Selenium Amongst Vegan and Vegetarian Women Highlight a Potential Nutritional Vulnerability - Fallon, Naomi; Dillon, Stephanie A. (Frontiers in Nutrition, 2020)
Vegan and vegetarian diets are becoming increasingly popular in the UK. Due to the avoidance of animal products there can be significant differences in nutrient intakes between meat-eaters and vegetarians, and especially vegans (2). Importantly, research has identified that both vegans and vegetarians may be vulnerable to low intakes of some micronutrients. The aim of this study was to investigate micronutrient intake in omnivorous, vegetarian and vegan women. In total, 62 women (26 omnivores, 16 vegetarians, 20 vegans, mean age 31.6±12.4y, mean BMI 24.1±1.6kg/m2) completed 4-day diet diaries. Diet intake data was analysed using Nutritics and nutrient intake levels were compared with national dietary recommendations (RNIs). Statistical analysis was performed using SPSS, with differences between the groups identified using ANOVA with post-hoc Bonferroni correction. All groups recorded intakes of vitamin D, iron, iodine and selenium below RNI. The vegan group had significantly lower intakes of vitamin D, vitamin B12, calcium, selenium and iodine than vegetarians and omnivores (p<.05), with particularly low intakes of selenium (24.7±11.9µg) and iodine (24.4±12.7µg). These results suggest that adult women in the UK are at risk of low intakes of several vitamins and minerals, with the exclusion of animal products conferring an additional vulnerability, particularly with respect to selenium and iodine, both of which play important roles in thyroid hormone production. This study highlights iodine and selenium intakes to be a concern amongst women who follow vegan diets, and the necessity of further research to identify if low intake translates to biochemical markers and functional status.